2010
DOI: 10.1590/s0037-86822010000200023
|View full text |Cite
|
Sign up to set email alerts
|

Malária vivax com tempo de incubação prolongado, detectada no Distrito Federal: relato de três casos

Abstract: RESUMOForam detectados três casos de malária vivax em Brasília, Distrito Federal, área considerada indene, procedentes da Amazônia, seis meses após estarem residindo em Brasília. Período de incubação prolongado tem sido descrito apenas para infecções por cepas de Plasmodium vivax de clima temperado. Não foi possível genotipar os parasitos. Palavras-chaves: Malária. Plasmodium vivax. Incubação prolongada. ABSTRACTThree cases of vivax malaria originating from the Amazon region were detected after living in Brasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Since malaria treatment is not supervised in the Amazon Region and the antimalarial dispensing system in health services is often precarious 2 , this hypothesis cannot be overlooked. Neither is it possible to rule out factors associated with the total administered dose of primaquine and the development of hypnozoite resistance to this drug in the region, as other researchers have suggested 3,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since malaria treatment is not supervised in the Amazon Region and the antimalarial dispensing system in health services is often precarious 2 , this hypothesis cannot be overlooked. Neither is it possible to rule out factors associated with the total administered dose of primaquine and the development of hypnozoite resistance to this drug in the region, as other researchers have suggested 3,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in Rio de Janeiro and Brasília have recently reported travelers with long incubation periods for malaria, varying from 3 to 12 months after returning from trips to the Amazon. They suggested that temperate strains coexist with the tropical strain in the country 22,27 . This hypothesis is corroborated by the observation of relapses at days 33, 73, 82, 88, 113, 121, and 137 after initiating therapy in a P. vivax malaria treatment cohort in 1990 in Cuiabá (Mato Grosso State), where malaria transmission does not occur 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In French Guiana the relapse rate in children was 70% (nearly all relapses occurred within three months) but both recrudescence and reinfection could not be excluded [114]. Although South American P. vivax is generally regarded as "tropical frequent relapsing" in phenotype, a recent report from Rio de Janeiro that six of 80 travellers presenting with vivax malaria (who had returned from the Amazon region and not received chemoprophylaxis) had an incubation period of between three to 12 months, and another from Brasilia describing long-latency in three patients, suggest that long-latency forms may coexist with frequent relapse phenotypes in Brazil [115,116]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by one of the authors of this report (Tauil PL) described three cases of vivax malaria originating from the Amazon region and diagnosed in Brasilia, Federal District, six months after departure from the endemic region in 2008 [13]. Two of those patients were infected in the same town (São Gabriel da Cachoeira, Amazonas State, Brazil), as one of the patients in the present study.…”
Section: Discussionmentioning
confidence: 55%